Effect of probiotics consumption level on anxiety and depression in maintenance hemodialysis patients - XIAO Xiao-fen; WANG Xiao-hui; WANG Jing; HAN Qi (Linchuang shenzangbing zazhi)
Objective To investigate the different levels of probiotics consumption in patients with maintenance hemodialysis(MHD), and to understand the effect of different consumption levels on their depression and anxiety. Methods A total of 102 patients with MHD were enrolled, and divided into different groups according to the consumption of probiotics including yogurt and intestinal microbial preparations(healthy foods or medicines other than yogurt) in the past six months. The self-rating anxiety scaling(SAS) and the self-rating depression scaling(SDS) were used to compare the differences of anxiety and depression scores between groups. Results Among all the included patients, 50 cases were the high-consumption of yogurt(49.02%), 29 cases were the high-consumption of intestinal microbial preparations(28.43%), and 79 cases were the high-consumption of probiotics(77.45%).The scores of SAS and SDS in the high-consumption yogurt group were lower than those in the low-consumption group, with statistically significant difference(P<0.05).The scores of SAS and SDS in the high-consumption intestinal microbial preparations group were significantly lower than those in the low-consumption group(P<0.05),and the scores of SAS and SDS in the high-consumption probiotics group also were significantly lower than those in the low-consumption group(P<0.05).The scores of SAS and SDS in the high-consumption yogurt group were significantly higher than those in the high-consumption intestinal microbial preparations group(P<0.05). Conclusions The higher the consumption level of probiotic products, the lower the SAS and SDS scores of MHD patients. Reasonable supplementation of probiotics may relieve the anxiety and depression of MHD patients. And it’s worth paying more attention to and exploring further the effect of probiotics on MHD patients’ emotion.